Annexin V Levels as an Indicator of Myocardial Cell Death after Myocardial Infarction - Karem Ahmed , Mohammed; Hassan Mohammed, Adil (Diyala Journal of Medicine, 2020)
Background:Myocardial ischemia is associated with apoptosis of cardiomyocyte and because of apoptotic cell death is characterized by externalization of Phosphatidylserine on the cell membrane, so it is amenable to targeting by Annexin V. Objective: To compare plasma concentrations of Annexin V in patients who had an early infarct with patients without infarction. And to analyze the plasma concentration of Annexin V in relationship to cardiovascular risk factors. Patients and Methods: A Case-control study of 100 patients (case) who are diagnosed with Myocardial Infarction (MI) and admitted to the coronary care unit of Baqubah Teaching Hospital and another 100 patients homogenous in terms of age and gender and who attended the hospital for other cause than myocardial infarction is selected as the control group during a period between the first of April and the first of July 2019. A special questionnaire used to collect the required information, an early morning blood sample is taken to measure the level of Annexin V by ELISA, Student’s t-test, ANOVA test and Chi_square test to find an association and differences between variables. Results: The results showed that The mean Annexin V level is significantly higher in cases (10.48155ng/ml) than control (1.28803ng/ml) with p-value =0.001 and a sample taken within 24 hours after MI is significantly higher in the mean level of Annexin V then the sample taken after 24 hours of MI. Conclusion: Generally, the measurement of Annexin V level has provided a good diagnostic test to evaluate myocardial infarction.